Intravascular ultrasound in children with congenital heart defects: a case series - N. M. Troshkinev; N. A. Kochergin; I. V. Ganyukov; R. S. Tarasov (Кардиоваскулярная терапия и профилактика)
Intravascular imaging methods are an actively developing area that was originally used in the treatment of coronary artery disease. With the help of intravascular ultrasound (IVUS), there is an opportunity to more objectively, in contrast to fluoroscopy, evaluate the vascular anatomy and lesion morphology, as well as optimize transcatheter interventions. In recent years, intravascular imaging has become widespread in the evaluation of children with congenital heart defects. A review of the literature on IVUS in endovascular treatment of congenital heart defects is presented and cases of the IVUS use in children with patent ductus arteriosus, descending aortic stenosis after interrupted aortic arch repair and pulmonary stenosis are presented.